literature review family support and schizophrenia relapse - Tessy Anggraini (Masker Medika, 2024)
Relapse in patients with schizophrenia is a complex mental health problem and is often influenced by various factors, including social support. This study aims to explore the relationship between social support and relapse in patients with schizophrenia. This study uses a literature study approach using several selected sources such as Google Scholar, ResearchGate, DOAJ and PubMed. Limited to the period 2013-2023 and from 20,700 GoogleScholar, 527 from DOAJ, 244 findings from PubMed. Furthermore, the literature was selected into 20 articles that met the inclusion criteria for the study. The results of this review are that positive emotional support from the family functions as a significant protective factor in preventing relapse. These findings emphasize the importance of psychosocial interventions involving families in supporting patients with schizophrenia, as well as the need for education for families to create an environment that supports recovery. Thus, strengthening social support networks and family involvement is essential to reduce the risk of relapse and improve the quality of life of patients.